Gamma scintigraphic study of the hydrodynamically balanced matrix tablets of Metformin HCl in rabbits - Razavi M; Karimian H; Yeong CH; Sarji SA; Chung LY; Nyamathulla S; Noordin MI (Dove Medical Press, 2015)
Mahboubeh Razavi,1 Hamed Karimian,1 Chai Hong Yeong,2 Sazilah Ahmad Sarji,2 Lip Yong Chung,1 Shaik Nyamathulla,1,3 Mohamed Ibrahim Noordin1,31Department of Pharmacy, Faculty of Medicine, 2Department of Biomedical Imaging and University of Malaya Research Imaging Centre, Faculty of Medicine, 3Department of Chemistry, Centre for Natural Products and Drug Discovery (CENAR), Faculty of Science, University of Malaya, Kuala Lumpur, MalaysiaAbstract: The purpose of this study is to evaluate the in vitro and in vivo performance of gastro-retentive matrix tablets having Metformin HCl as model drug and combination of natural polymers. A total of 16 formulations were prepared by a wet granulation method using xanthan, tamarind seed powder, tamarind kernel powder and salep as the gel-forming agents and sodium bicarbonate as a gas-forming agent. All the formulations were evaluated for compendial and non-compendial tests and in vitro study was carried out on a USP-II dissolution apparatus at a paddle speed of 50 rpm. MOX2 formulation, composed of salep and xanthan in the ratio of 4:1 with 96.9% release, was considered as the optimum formulation with more than 90% release in 12 hours and short floating lag time. In vivo study was carried out using gamma scintigraphy in New Zealand White rabbits, optimized formulation was incorporated with 10 mg of 153Sm for labeling MOX2 formulation. The radioactive samarium oxide was used as the marker to trace transit of the tablets in the gastrointestinal tract. The in vivo data also supported retention of MOX2 formulation in the gastric region for 12 hours and were different from the control formulation without a gas and gel forming agent. It was concluded that the prepared floating gastro-retentive matrix tablets had a sustained-release effect in vitro and in vivo, gamma scintigraphy played an important role in locating the oral transit and the drug-release pattern.Keywords: gastro-retentive drug delivery, natural polymer, gamma scintigraphy, sustain release formulation, salep, tamarind seed